PENYELESAIAN SENGKETA PERDATA MELALUI GUGATAN SEDERHANA (SMALL CLAIM COURT) DI PENGADILAN NEGERI MAKASSAR TAHUN 2023 - Nur, Syamsuddin (Universitas 17 Agustus 1945 Samarinda, 2024)
The dispute resolution process allows the court to settle cases based on the value of the object of the dispute, so that dispute resolution can be carried out quickly, easily and at low cost. According to PERMA Number 2 of 2015, the value of the case object should not exceed Rp.200,000,000.00 (two hundred million rupiah), with a simple evidentiary process and presided over by one judge with the event The process of resolving civil disputes through the settlement of simple lawsuits at the Class 1 A District Court of Makassar includes registration of simple lawsuits, examination of simple lawsuits, determination of judges, and appointment of substitute clerks.